Spin Current Generation at the Hybrid Ferromagnetic Metal/Organic Semiconductor Interface as Revealed by Multiple Magnetic Resonance Techniques - Kohei Takaishi; Haruka Tsutsumi; Hideto Matsuoka; Takayuki Suzuki; Katsuichi Kanemoto (Advanced Electronic Materials)
Abstract Understanding and controlling the hybrid interface of ferromagnetic (FM) metal/organic semiconductor (OS) is critical for realizing efficient spin polarization transfers. Here, multilayer devices composed of FM metal and OS with extremely long spin relaxation time are prepared, for which the correlation between spin current properties and interfacial electronic states is investigated using multiple magnetic resonance techniques. These multilayer devices exhibit a narrower ferromagnetic resonance linewidth compared to FM single‐layer devices, despite generating spin currents by spin‐pumping, which challenges conventional understanding. This narrower linewidth results from the formation of hybrid electronic states at the FM/OS interface. The OS layer employed enables the detection of electron paramagnetic resonance (EPR) signals even in thin films, indicating that FM and OS spins mix across the hybrid interface and that the inflow of FM spins for spin current generation significantly increases the EPR linewidth. These findings highlight the importance of the interfacial design between FM metals and OSs for efficient spin current generation and pave the way for new explorations of hybrid interfacial electronic states.